Biosynthesis of silver nanoparticles with antioxidant and bactericidal activities using Capsicum annuum fruit extract - V. Kalynovskyi; O. Smirnov; P. Zelena; Y. Yumyna; M. Kovalenko; V. Dzhagan; M. Dzerzhynsky; N. Taran (Regulatory Mechanisms in Biosystems, 2023)
Metallic nanostructures, especially silver nanoparticles (AgNPs) have already found multiple applications in modern industry, science and medicine. Still, the production of nano-sized compounds often leads to the formation of toxic byproducts and possesses substantial environmental hazard. One of the promising solutions for the ecofriendly creation of nanomaterials predicts the use of a “green chemistry” approach using organisms, their parts or natural compounds to act as safe and effective producers of nanomaterials. Plant-mediated biosynthesis of silver nanoparticles includes the reduction of Ag+ to Ag0 by natural compounds, usually secondary metabolites which can be found in roots, leaves, cortex, fruits, flowers and seeds of various species. Aqueous extract of Capsicum annuum var. cv. (cultivar) Teja (S-17) fruits was used as a bioreducer for the reduction of AgNO3 solution to AgNPs. The formation of the AgNPs was confirmed by the presence of the Tyndall effect of light scattering combined with colour change of the solutions. The properties of the nanoparticles were assessed with UV-visible spectroscopy and scanning electron microscopy. In the present study, we report the experimental optimization of operating parameters needed for silver biotransformation by C. annuum. Biosynthesized nanoparticles were 13–22 nm in size and spherical in shape. Colloidal solutions of AgNPs were also confirmed to show antioxidant activity in vitro as analyzed by the reduction of DPPH radicals. Characterization and application of AgNPs as bactericidal agents on two Gram-positive (Micrococcus luteus, Staphylococcus aureus) and two Gram-negative (Escherichia coli, Pseudomonas aeruginosa) prokaryotic microorganisms demonstrated the prevalent influence on Gram-positive strains.